Desenvolvimento e implantação de solução para comunicação bidirecional de longo alcance com medidores de energia elétrica - Adam, Leonardo (2022)
In recent years, the electricity generation, transmission and distribution has gone through changes. New kinds of loads are inserted on the grid, technologies are being introduced and new standards are being estabilished. With that, there is a requirement of a better monitoring across the whole system, especially on the distribution sector, the sector that has the greatest technological lack in the system. Thus, this master thesis presents the development and the implementation of a solution for a long range bidirectional communication with energy meters of group B consumers with LoRa network. The requirements to the development of a device that should integrate the energy meters with the data management system are defined. Then, the methodology for developing the hardware and firmware of the device are presented, as the structure for the data management software. Also, the results of simulations, laboratory and field tests related to the device-meter and long range communication are presented. Finally, the achieved results are discussed and suggestions to improve the system are done.